Epidemiological Description of Cystic Ovarian Disease in Argentine Dairy Herds: Risk Factors and Effects on the Reproductive Performance of Lactating Cows - Cattáneo, Luciano (2014)
To describe the epidemiology of cystic ovarian disease (COD), to find possible risk factors associated with the incidence of cysts and to analyse the impact of COD on the reproductive performance of dairy cows, databases from 22 dairy herds from the main dairy region in Argentina were retrospectively evaluated throughout a 3‐year period (2009–2011). A total of 248 COD cases over 9156 parturitions were recorded, resulting in a cumulative incidence rate of 2.7%. Cystic ovarian disease incidence density was lower during the first 100 days post‐partum (DPP) than during later stages of lactation. Seasonality had a significant influence on the disease presentation with higher incidence rates during winter and spring. Cows with a previous diagnosis of clinical mastitis showed 2.72 times more chances of developing ovarian cysts. Cystic cows had longer calving to first service and calving to conception intervals and lower conception rate than controls.